Cytokines that Modulate the Differentiation of Th17 Cells in Autoimmune Uveitis - Kailei Guo; Xiaomin Zhang (Journal of Immunology Research)
Increasing evidence has suggested that T helper 17 (Th17) cells play a central role in the pathogenesis of ocular immune disease. The association between pathogenic Th17 cells and the development of uveitis has been confirmed in experimental and clinical studies. Several cytokines affect the initiation and stabilization of the differentiation of Th17 cells. Therefore, understanding the mechanism of related cytokines in the differentiation of Th17 cells is important for exploring the pathogenesis and the potential therapeutic targets of uveitis. This article briefly describes the structures, mechanisms, and targeted drugs of cytokines—including interleukin (IL)-6, transforming growth factor-β1 (TGF-β1), IL-1β, IL-23, IL-27, IL-35, IL-2, IL-4, IL-21, and interferon (IFN)-γ—which have an important influence on the differentiation of Th17 cells and discusses their potential as therapeutic targets for treating autoimmune uveitis.